THE EFFECTIVENESS OF KENYA’S COUNTERTERRORISM MEASURES SINCE 1998. - Dr. Joseph Wamocha Nasongo (International Journal of Research Science and Management, 2018)
Terrorism is a contemporary security threat not only to Kenya but also the international community of nations. Measures put in place to combat this threat by individual nations and the international community have achieved varied results. Whereas to a significant extent, successes have been realized, terrorism continues to threaten security due its dynamic and fast evolving nature. This study embarked on an examination of the counter terrorism measures since 1998. The objective of the study was to examine the effectiveness of counterterrorism measures put in place by the Kenya government since 1998. Within the context of qualitative research paradigm and explanatory research design, the researcher adopted historical research method The sources for data included: journals, internet data bases on terrorism, newspaper articles, text books, position papers on the subject, government policy documents, status papers on terrorism from the national counter terrorism centre, theses and projects reports. The findings of the study revealed that terrorism is real as evidenced by series of attacks that have led to over 1000 deaths, thousands of injuries and destruction of property. The trends of terror attack followed a pattern and the tempo of attacks increased markedly after KDF invaded Southern Somalia in 2011. It was also established that the combined efforts of AMISOM and support from the international community has succeeded in uprooting Al-Shabaab from its strongholds, but continue to be lethal operating in smaller groups using new tactics. With regard to Kenya’s counterterrorism measures, it was established that the country has put in place a range of measures. They include: expansion of number of security forces, acquisition of new skills and technical expertise, purchase of sophisticated military hardware, improved intelligence gathering capacity, establishment of centralized command system, enactment of legislations, and more importantly, development and implementation of national strategy for countering violent extremism that is all inclusive. There is also increased funding to the security sector. International support has also been invaluable. The support has ranged from shared intelligence, military training, sharing of experiences, fiscal support, and technology transfer. In conclusion, the study observes that the threat of terrorism is far from being won. The resolve to defeat the terrorists must be sustained through alleviation of structural causes of violent extremism, step up strategies of countering violent extremism to complement military and security operations approaches.